2021
DOI: 10.1038/s43247-021-00267-8
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and nanoplastics barely enhance contaminant mobility in agricultural soils

Abstract: Farmland soils are prone to contamination with micro- and nanoplastics through a variety of agricultural practices. Concerns are recurrently raised that micro- and nanoplastics act as vector for organic contaminants to deeper soil layers and endanger groundwater resources. Whether and to what extent micro- and nanoplastics facilitate the transport of organic contaminants in soil remains unclear. Here we calculated the ratio between transport and desorption time scales using two diffusion models for micro- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 75 publications
0
22
0
1
Order By: Relevance
“…A study by Hüffer et al ( 2018 ) found that the polymer surface of PS micro (nano) plastics could become oxidized over time in the environment, making them more likely to interact with living things or adsorb organic contaminants. Castan et al ( 2021 ) evaluated the partitioning and diffusion coefficients for PE and tire-wear micro (nano) plastics bound contaminant migration (agrochemicals or pesticides such as hexachlorobenzene, endrin, aldrin, dichlorodiphenyltrichloroethane, transnonachlor, and additives such as polychlorinated biphenyls) in soil, and found rapid desorption. They were skeptical about micro (nano) plastics’ ability to assist pollutant migration or mobility.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Hüffer et al ( 2018 ) found that the polymer surface of PS micro (nano) plastics could become oxidized over time in the environment, making them more likely to interact with living things or adsorb organic contaminants. Castan et al ( 2021 ) evaluated the partitioning and diffusion coefficients for PE and tire-wear micro (nano) plastics bound contaminant migration (agrochemicals or pesticides such as hexachlorobenzene, endrin, aldrin, dichlorodiphenyltrichloroethane, transnonachlor, and additives such as polychlorinated biphenyls) in soil, and found rapid desorption. They were skeptical about micro (nano) plastics’ ability to assist pollutant migration or mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the quality of agricultural products and the growth and photosynthesis of plants are altered by the presence of microplastics (YANG et al, 2021). Importantly, microplastics can adsorb and transport contaminants such as heavy metals and other pollutants in the soil environment (CASTAN et al, 2021,). Lastly, direct ingestion of microplastics or consumption through contaminated food, such as fish and agricultural products, is a threat to human health (MO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…under the influence of sunlight, temperature, humidity and wind, which account for 70-80% of all plastic released into the environment ( Lambert and Wagner, 2016 ; Kiran et al., 2022 ). Most plastic pollution comes from anthropogenic activities, such as tire wear run off from roads, packaging, building materials, fishing gears, automotive parts, electronic utilities and agro-industry components ( Geyer et al., 2017 ; Horton et al., 2017 ; Pinto Da Costa et al., 2020 ; Kiran et al., 2022 ; Law and Narayan, 2022 ; Castan et al., 2021 ; Huang et al., 2022 ), as well as from atmospheric transport (e.g. wind drift) ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%